Trade and Growth under Limited Liberalization - Marina Bakanova; Lúcio Vinhas de Souza (Tinbergen Institute, 2002)
This paper studies the connection between trade and growth in the context of a partial and inconsistent liberalization process in a specific Eastern European country in transition towards market economy, namely, the Republic of Belarus. The analysis of the country trade patterns during the USSR period and the years since independence revealed that unlike its close neighbors (the Baltic States and Poland) Belarus did not succeed in changing the commodity or the geographical structure of its trade. It is almost a good representation of reality to say that Belarus trades with Russia. The assessment of the rationale for the closer integration with Russia and the impact of this process on Belarus growth led us to the conclusion that the integration in the form of a non-exclusive Free Trade Area and within the framework of a wider set of international connections rather than the move towards a Customs Union (and a Union State) with Russia would be a more optimal policy for Belarus. This conclusion is supported by the results of country-specific growth regressions and of a counterfactual free trade experiment via a small CGE model.
Keywords: F14; F15; F17; O47; P2; 330; CGE models; growth; transition economics; international trade; economic integration; Exportinduziertes Wachstum; Handelsliberalisierung; Übergangswirtschaft; Allgemeines Gleichgewicht; Weißrussland